2007
DOI: 10.1523/jneurosci.2712-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Memory Traces for Olfactory Reward Learning inDrosophila

Abstract: Physical traces underlying simple memories can be confined to a single group of cells in the brain. In the fly Drosophila melanogaster, the Kenyon cells of the mushroom bodies house traces for both appetitive and aversive odor memories. The adenylate cyclase protein, Rutabaga, has been shown to mediate both traces. Here, we show that, for appetitive learning, another group of cells can additionally accommodate a Rutabaga-dependent memory trace. Localized expression of rutabaga in either projection neurons, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 50 publications
3
107
1
Order By: Relevance
“…Similar dissociations have been reported previously for the Drosophila dunce mutant that affects immediate aversive, but not appetitive, memory (Tempel et al, 1983). In general, it is commonly accepted that aversive and appetitive odor learning depend on different neuronal circuits but share a requirement for MB KCs (Thum et al, 2007). The dissociation between the functional redundancies of either mouse Nbea or fly rgϩ transgenes is well in line with the hypothesis that different functional domains are required to support either type of odor learning.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar dissociations have been reported previously for the Drosophila dunce mutant that affects immediate aversive, but not appetitive, memory (Tempel et al, 1983). In general, it is commonly accepted that aversive and appetitive odor learning depend on different neuronal circuits but share a requirement for MB KCs (Thum et al, 2007). The dissociation between the functional redundancies of either mouse Nbea or fly rgϩ transgenes is well in line with the hypothesis that different functional domains are required to support either type of odor learning.…”
Section: Discussionsupporting
confidence: 84%
“…Here, aversive and appetitive memories can be compared in a site-bysite manner (Schwaerzel et al, 2003). The quality of the behavioral reinforcer used during the training procedure, i.e., either sugar reward for appetitive learning or electric shock punishment for aversive learning, influences the neuronal circuits (Krashes et al, 2007(Krashes et al, , 2009Pitman et al, 2011) required to establish an appropriate memory at the level of the Drosophila MBs (Schwaerzel et al, 2003;Thum et al, 2007). When assayed for immediate aversive or appetitive memory performance, rg 1 and rg ␥5 animals show a significant reduction compared with wild-type Canton-S controls.…”
Section: Resultsmentioning
confidence: 99%
“…In the cockroach, octopaminergic neurons with more or less similar morphology have been found (Sinakevitch, Niwa, & Strausfeld, 2005) and we speculate that some of these neurons convey sucrose US to various protocerebral areas. Roles of octopaminergic neurons for acquisition (Farooqui, Vaessin, & Smith, 2004;Nakatani, Matsumoto, Mori, Hirashima, Nishino, Arikawa, & Mizunami, 2009;Schroll, Riemensperger, Bucher, Ehmer, Voller, Erbguth, Gerber, Hendel, Nagel, Buchner, & Fiala, 2006;Schwaerzel et al, 2003;Unoki, Matsumoto, & Mizunami, 2005 In honey bees and fruit-flies, it has been suggested that both the MB and AL are the sites of association of olfactory CS and sucrose US for olfactory conditioning (Davis, 2005;Hammer & Menzel, 1998;Thum et al, 2007). For example, pharmacological inactivation of the MB during the differential conditioning trials was not impaired olfactory memory acquisition, suggesting that output region of MB do not involve in the olfactory differential conditioning (Devaud, Blunk, Podufall, Giurfa, & Grünewald, 2007).…”
Section: Neural Pathways Mediating Conditioned Olfactory Responses Ofmentioning
confidence: 99%
“…Critical issues in the study of olfactory learning are in which neurons and by what molecular mechanisms the olfactory conditioning stimulus (CS) is associated with appetitive or aversive unconditioned stimulus (US) in the central olfactory pathways. It has been suggested, in insects, that neurons in the AL and MB play critical roles in the CS-US association (Cano Lozano, Armengaud, & Gauthier, 2001;Davis, 2005;Gerber, Tanimoto, & Heisenberg, 2004;Heisenberg, 2003;Menzel, 1999), and also that these neurons receive olfactory CS from cholinergic neurons (Gu & O'Dowd, 2006), in addition to appetitive and aversive US from octopaminergic and dopaminergic neurons, respectively (Hammer, 1993;Hammer & Menzel, 1998;Schwaerzel, Monastirioti, Scholz, Friggi-Grelin, Birman, & Heisenberg, 2003;Thum, Jenett, Ito, Heisenberg, & Tanimoto, 2007). However, the types of ACh receptors used by these neurons remained unknown, and this has hampered the progress of study of cellular and molecular mechanisms of olfactory conditioning.…”
Section: Introductionmentioning
confidence: 99%
“…This, together with the strength of the phenotypic differences and the differences in anatomical requirements for G(o) activation and rut, argues against a direct interaction between the cAMP pathway and G(o) activation during negatively reinforced memory formation. In positively reinforced memory, rut is required in the a ′ /b ′ neurons and the projection neurons of the antennal lobe (Thum et al 2007). Thus, the role for G(o) activation in positively reinforced memory also maps outside the rut domains and, therefore, is also rut-independent.…”
Section: Heterotrimeric G(o) Signalingmentioning
confidence: 99%